KARAKTERISTIK FISIK DAN INDEKS IRITASI PADA SEDIAAN SHOOTING GEL KOMBINASI LIDAH BUAYADAN BUAH ANGGUR - Suharsanti, Ririn; Ariyani, Lilies Wahyu (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2018)
ABSTRACT Shooting gel is one of cosmetic preparations that work to overcome dry skin. High active ingredients in shooting gel are considered able to rehydrate the skin, especially dry skin. In this research will be formulated shooting gel preparation with active ingredients ofAloe vera and grapes. The famous Aloe vera helps to moisturize the skin while the grapes also contain active compounds that are efficacious as antioxidants that are good for the skin. Therefore, the combination of these two active ingredients should be developed on the shooting gel preparation. This study aims to see the spread, stickiness, pH, viscosity, irritation of shooting gel with variations of concentration of active ingredients of Aloe vera and grapes. This research was started with formulation of shooting gel preparation with combination concentration of active ingredient 80% (FI); 85% (FII); 90% (FIII). Shooting gel is evaluated physical characteristics with parameters spreadibility, adhesivity,viscosity and pH. It was also evaluated the irritation index of the skin using male rats. The data obtained were analyzed with different 95% confidence level test to know the existence of significant difference between treatment groups. The experimental results of shooting gel physical characteristics showed that the concentration variation did not affect the adhesivity (p> 0.05) but affects pH, viscosity and spreadibility (p <0.05). Shooting gel with all three concentrations did not irritate the skin of male rats.